Quality of care in patients with inflammatory bowel disease from a public health center in Brazil - Takamune, Debora Mayumi [UNESP]; Cury, Giovana Signorelli Astolfi [UNESP]; Ferrás, Giulia [UNESP]; Herrerias, Giedre Soares Prates [UNESP]; Rivera, Adriana; Barros, Jaqueline Ribeiro [UNESP]; Baima, Julio Pinheiro [UNESP]; Saad-Hossne, Rogerio [UNESP]; Sassaki, Ligia Yukie [UNESP] (Baishideng Publishing Group, 2022)
BACKGROUND Inflammatory bowel diseases (IBDs) are chronic diseases that demand continuous interaction between patients and healthcare providers. Quality of care (QoC) is a factor that contributes to a patient’s adherence to treatment and its success. AIM To evaluate QoC in patients from a single IBD reference center. METHODS This cross-sectional study included 133 patients from a single Brazilian IBD public health center. QoC was evaluated through the QoC Through the Eyes of Patients with IBD (QUOTE-IBD) questionnaire (based on patient perspectives), which measures eight dimensions of care. We compared QoC among patients with Crohn’s disease and ulcerative colitis and analyzed the clinical and psychological factors associated with QoC satisfaction. Clinical evaluations assessed disease characteristics, quality of life, anxiety, and depression levels. RESULTS Sixty-nine patients with Crohn’s disease and 64 with ulcerative colitis were interviewed. The mean age was 37.26 years ± 13.05 years, and 63.91% of the patients were women. The mean duration of the disease was 8.44 years ± 7.59 years, where most patients were in remission (70.31% of patients with ulcerative colitis and 62.32% with Crohn’s disease). The total QoC score of the sample was 8.61 years ± 1.31 points, indicating that the QoC provided by the center was unsatisfactory. According to univariate logistic regression, patients with Crohn’s disease had higher satisfaction rates than those with ulcerative colitis [odds ratio (OR): 2.746; 95% confidence interval (CI): 1.360-5.541; P = 0.0048] and patients on infliximab (OR: 2.175; 95%CI: 1.037-4.562; P = 0.0398). CONCLUSION Patients from the IBD public center reported good doctor-patient relationships, but had problems related to the healthcare structure. Evaluation of healthcare centers is of paramount to improve QoC for the patients involved.
Keywords: Crohn’s disease; Doctor-patient relationship; Inflammatory bowel disease; Quality of care; Quote-ibd questionnaire; Ulcerative colitis